(untitled) (Research, Society and Development, 2019)
In Brazil the initial formation of teachers emerged after the independence of the country, during which period the organization of popular instruction was considered. From this, began to the creation of the Normal schools, with the scope to train and to train the teachers. In the state of Maranhão, the University State of Maranhão (UEMA) has strengthened teacher training, with the offer of undergraduate courses, thus showing its vocation in the graduation of teachers. Therefore, the central objective of the article was to record the contributions made by the Center for Higher Studies of Balsas (CESBA) UEMA’s campus with the training, qualification and initial qualification of teachers for the South-Maranhão society. For the accomplishment of the study, it was necessary to be guided in the bibliographical research; documentary, in the Pedagogical Projects of Courses and in the field research, with the application of questionnaires to the graduates of the degrees. The application of the questionnaires to the investigated public sought to discover the opinions regarding the aspects of the professional training in said Center. As a result, three categories of analysis were established: 1. CESBA’s educational philosophy for teacher training; 2. Objectives, competencies and skills in teacher training; 3. Perceptions regarding initial teacher education. Finally, these studies have allowed us to understand part of the history of the formation of initial teacher training, to perceive factors that have been preserved, what has changed, and mainly, what needs improvement.